Features of severe COVID‐19: A systematic review and meta‐analysis - Del Sole, Francesco (Eur J Clin Invest, 2020)
BACKGROUND: To systematically review clinical and biochemical characteristics associated with the severity of the novel severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)‐related disease (COVID‐19). MATERIALS AND METHODS: Systematic review of observational studies from PubMed, ISI Web of Science, SCOPUS and Cochrane databases including people affected by COVID‐19 and reporting data according to the severity of the disease. Data were combined with odds ratio (OR) and metanalysed. Severe COVID‐19 was defined by acute respiratory distress syndrome, intensive care unit admission and death. RESULTS: We included 12 studies with 2794 patients, of whom 596 (21.33%) had severe disease. A slightly higher age was found in severe vs non‐severe disease. We found that prevalent cerebrovascular disease (odds ratio [OR] 3.66, 95% confidence interval [CI] 1.73‐7.72), chronic obstructive pulmonary disease (OR: 2.39, 95% CI 1.10‐5.19), prevalent cardiovascular disease (OR: 2.84, 95% CI 1.59‐5.10), diabetes (OR: 2.78, 95% CI 2.09‐3.72), hypertension (OR: 2.24, 95% CI 1.63‐3.08), smoking (OR: 1.54, 95% CI 1.07‐2.22) and male sex (OR: 1.22, 95% CI 1.01‐1.49) were associated with severe disease. Furthermore, increased procalcitonin (OR: 8.21, 95% CI 4.48‐15.07), increased D‐Dimer (OR: 5.67, 95% CI 1.45‐22.16) and thrombocytopenia (OR: 3.61, 95% CI 2.62‐4.97) predicted severe infection. CONCLUSION: Characteristics associated with the severity of SARS‐CoV‐2 infection may allow an early identification and management of patients with poor outcomes.